Characterization of aromatase expression in the adult male and female mouse brain. I. Coexistence with oestrogen receptors α and β, and androgen receptors. - Davor Stanić (Public Library of Science (PLoS), 2014)
Aromatase catalyses the last step of oestrogen synthesis. There is growing evidence that local oestrogens influence many brain regions to modulate brain development and behaviour. We examined, by immunohistochemistry, the expression of aromatase in the adult male and female mouse brain, using mice in which enhanced green fluorescent protein (EGFP) is transcribed following the physiological activation of the Cyp19A1 gene. EGFP-immunoreactive processes were distributed in many brain regions, including the bed nucleus of the stria terminalis, olfactory tubercle, medial amygdaloid nucleus and medial preoptic area, with the densest distributions of EGFP-positive cell bodies in the bed nucleus and medial amygdala. Differences between male and female mice were apparent, with the density of EGFP-positive cell bodies and fibres being lower in some brain regions of female mice, including the bed nucleus and medial amygdala. EGFP-positive cell bodies in the bed nucleus, lateral septum, medial amygdala and hypothalamus co-expressed oestrogen receptor (ER) α and β, or the androgen receptor (AR), although single-labelled EGFP-positive cells were also identified. Additionally, single-labelled ERα-, ERβ- or AR-positive cell bodies often appeared to be surrounded by EGFP-immunoreactive nerve fibres/terminals. The widespread distribution of EGFP-positive cell bodies and fibres suggests that aromatase signalling is common in the mouse brain, and that locally synthesised brain oestrogens could mediate biological effects by activating pre- and post-synaptic oestrogen α and β receptors, and androgen receptors. The higher number of EGFP-positive cells in male mice may indicate that the autocrine and paracrine effects of oestrogens are more prominent in males than females.